2021
DOI: 10.1183/13993003.04168-2020
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a novel subset of alveolar type 2 cells enriched in PD-L1 and expanded following pneumonectomy

Abstract: Alveolar type 2 (AT2) cells are heterogeneous cells; where specialised AT2 subpopulations within this lineage exhibit stem cell properties. However, the existence of quiescent, immature cells within the AT2 lineage, which are activated during lung regeneration, is unknown.SftpcCreERT2/+; tdTomatoflox/flox mice were used for the labelling of AT2 cells and labeled subpopulations were analysed by flow cytometry, qPCR, ATAC-seq, gene arrays, pneumonectomy, and culture of precision-cut lung slides. ScRNA-seq data f… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

21
70
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2
1

Relationship

4
4

Authors

Journals

citations
Cited by 38 publications
(91 citation statements)
references
References 29 publications
21
70
0
Order By: Relevance
“…In Choi's paper, the authors, using as a model the bleomycin-treated mice, confirmed interleukin 1β (Il-1β) as a possible inducer of the transitional state. The gene signature of primed AT2 cells corresponded to an activated immune state, similar to what is reported in Ahmadvand's paper more recently (Ahmadvand et al, 2021). In Choi's paper, they identified IM as the source of Il-1β.…”
Section: Better Characterization Of the Interaction Of At2s With Immune Cellssupporting
confidence: 82%
See 2 more Smart Citations
“…In Choi's paper, the authors, using as a model the bleomycin-treated mice, confirmed interleukin 1β (Il-1β) as a possible inducer of the transitional state. The gene signature of primed AT2 cells corresponded to an activated immune state, similar to what is reported in Ahmadvand's paper more recently (Ahmadvand et al, 2021). In Choi's paper, they identified IM as the source of Il-1β.…”
Section: Better Characterization Of the Interaction Of At2s With Immune Cellssupporting
confidence: 82%
“…It is therefore extremely difficult to identify a specific role for each player. For the AT2 cells, our recently published work suggests that a subpopulation of quiescent and relatively undifferentiated AT2 cells, positive for the immune marker PD-L1, could be a major partner for the immune cells (Ahmadvand et al, 2021). In addition, Fgf10 signaling via Fgfr2b in AT2 cells appears to control the expression of immune markers (Chao et al, 2017).…”
Section: What's Next? Better Characterization Of the At2 Cellsmentioning
confidence: 97%
See 1 more Smart Citation
“…The physiological involvement of iAT2 cell-mediated inflammation in the loss of parenchymal structure may be further strengthened by a recent report, which showed that the existence of β1 integrin-deficient AT2 with upregulation of NF-κB-dependent chemokines was sufficient for developing accelerated inflammation 42 . A recent paper suggested the existence of a novel subpopulation of AT2 with high PD-L1 but low SFTPC expression in IPF 43 . Despite the common characteristic of high PD-L1 expression, we recognize substantial differences between our iAT2 and AT2 subpopulations.…”
Section: Discussionmentioning
confidence: 99%
“…Despite these diverse biological activities during development and repair after injury, Fgfr2b signaling in AT2s has been deemed dispensable during homeostasis [14, 18]. Notably, the respective function of Fgfr2b signaling in our recently described, lineage-traced, AT2 subpopulations has not been defined [19].…”
Section: Introductionmentioning
confidence: 99%